Optimized techniques for the extraction of grape allergens appropriate for in vivo and in vitro testing and diagnosis - Vassilopoulou, E. V.; Zuidmeer, L.; Akkerdaas, J.; Rigby, N.; Moreno, F. J.; Papadopoulos, N. G.; Saxoni-Papageorgiou, P.; Mills, C.; van Ree, R. (Mol Nutr Food Res, 2007)
Standardized allergen extracts are needed for diagnosis and therapy purposes. For grapes, standardization is hampered by low protein and high tannin and pectin concentrations. The aim of the current study was to develop an optimized method for the extraction of grape proteins and possibly extend this to other fruits. Several existing or modified extraction methods were compared by means of protein concentration determination, SDS-PAGE, immunoblotting and radioallergosorbent test (RAST). An optimized extraction protocol was obtained in which we combined a high concentration of plant tissue, a concentrated, enriched and neutral buffer able to remove sugars and keep proteins soluble and a bivalent buffer for pectin removal. Both the quantitative (protein concentration) and qualitative parameters (SDS-PAGE protein patterns and IgE reactivity) were compared to standard protocols and commercial extracts used as diagnostic tools in the clinical practice. This method proved to be the most efficient mainly compared to the standard Björksten protocol in extracting the low molecular weight proteins, including the major grape allergen (lipid transfer protein, Vit v 1). It proved to be an easy, low cost and reproducible method proposed to prepare grape extracts that could replace the commercially available ones, used for diagnosis and possibly extend the method to other fruits especially in extracting LTPs.
Keywords: Adolescent Adult Allergens Child Electrophoresis; Polyacrylamide Gel Female Food Hypersensitivity Fruit Humans Immunoglobulin E Male Radioallergosorbent Test Skin Tests Vitis